National Geographic Magazine [computer file] The 1960s (vol. 136, no. 6, December 1969) Jan. 1960-April 1963, May 1963-August 1966, September 1966-December 1969 (The Complete National Geographic : 110 years of National Geographic Magazine on CD-ROM, 1888)
Once again, mourn the death of President Kennedy, assassinated less than one month before he was to dedicate the new Geographic headquarters building, through the minute-by minute accounts of the country's final tribute. Witness Louis Leakey's breathtaking discovery of the first traces of early man in the Olduvai Gerge. Journey to space and walk on the moon with crew of Apollo 11. And experience many more captivating moments from the 1960s.